Records of air temperature, monsoon precipitation, and vegetation type over the past 200 kyr based on lipid biomarkers preserved at Lingtai on the central CLP - Louise Fuchs; Bin Zhou; Clayton Magill; Timothy Ian Eglinton; Youbin Sun; Francien Peterse (PANGAEA, 2022)
The Lingtai section is situated in the central part of the CLP at ~1340 m above sea level (35°04 extquotesingleN, 107°39 extquotesingleE). Long chain n-alkane plant waxes and brGDGTs were analysed in 10 cm thick layers collected at 0.5 m intervals from the upper 18.5 m of the LPS. The section covers the past 200 ka based on the correlation of the quartz grain size record from Lingtai (Sun et al., 2006) with the global benthic d18O stack (Lisiecki and Raymo, 2005), resulting in an average resolution of our records of ~5 ka. From the detected biomarker distributions and their stable isotopic composition, we generated records of vegetation change based on the ACL and the weighed mean of the carbon isotopic composition of the most abundant plant waxes, i.e. the C29, C31, and C33 n-alkanes (δ13Cwax), precipitation using the hydrogen isotopic composition of the same suite of n-alkanes (δ2Hwax), and finally MAT for months above freezing using the MBT extquotesingle5ME index (De Jonge et al., 2014) and the BayMBT0 model (Dearing Crampton-Flood et al., 2020).